KONTRIBUSI DANA WAKAF TERHADAP KESEJAHTERAAN UMKM BINAAN KSPPS MANDIRI SEJAHTERA - Cantika Agustia; Rachma Indrarini; Sri Abidah Suryaningsih; A'rasy Fahrullah (LPPM STAI Muhammadiyah Probolinggo, 2026)
MSMEs (Micro, Small and Medium Enterprises) are one of the main economic sectors that contribute greatly to economic development in Indonesia. In its development, every MSME needs funding for the development of its business. Financial institutions play an important role in helping funding for MSMEs. One of the financial institutions that assists MSMEs in achieving their funding is the Sharia microfinance institution, namely Baitul Maal Wat Tamwil. One of the functions of BMT as a social institution is that BMT has a program that combines economic and social functions by empowering waqf funds for MSMEs. This study uses a descriptive qualitative research method that functions to determine the role of the waqf fund empowerment program for the welfare of MSMEs fostered by KSPPS BMT Mandiri Sejahtera East Java. Based on the results of the research carried out, it was found that the waqf fund empowerment program carried out by KSPPS BMT Mandiri Sejahtera plays a role as a capital provider and has a positive role in helping fostered MSMEs achieve prosperity based on sharia maqashid indicators.